Seismotectonic characteristics of the Cugenang Fault, Cianjur, West Java, based on a-value, b-value, seismic moment and satellite gravity (earthquake data of 2008 - 2023) - Prihatini, Atin; Indrianai, Rina Dwi; Setyawan, Agus; Fahmi, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2025)
The formation of fault in Cugenang, Cianjur Regency, West Java, caused an earthquake on 21 November 2022, with a magnitude of 5.6 SR, resulting in significant losses and casualties. The orientation of the Cugenang fault is N 347° E, dip 82.8°, depth 10 - 11 km, and a dextral strike-slip mechanism. This research aims to analyze the seismotectonic activity in the Cianjur area using a-value, b-value, seismic moment, and gravity field anomaly data. The processing of the b-value, a-value, and seismic moment was conducted using earthquake data from the Indonesia Meteorology and Geophysics Agency’s website, which includes longitude, latitude, magnitude, and earthquake depth (1 January 2008 - 28 February 2023). Gravity field anomalies were processed using GGMplus satellite data. The results indicate that residual gravity anomaly values and seismic moments are inversely proportional to the a-value and b-value. The seismic moment values range from 12.2 to 14.7, the b-value from 0.2 to 1, the a-value from 1.1 to 2.1, and the residual gravity anomaly is -16 mGal to 26 mGal. The earthquake’s epicenters were distributed north of the Cimandiri fault in the Rajamandala segment, coinciding with the location of the Cugenang fault. The average earthquake depth ranged from 10 km to 20 km, suggesting that the earthquakes occurred in young volcanic rocks. The presence of active faults and brittle volcanic rocks makes the area around Cianjur prone to earthquakes and increases the potential for additional new faults.